THE IMPACT OF SERVICE QUALITY ON THE EMOTIONAL WELL-BEING OF STUDENTS: A STUDY AMONGST COLLEGE STUDENTS IN KUALA LUMPUR, MALAYSIA - Kanesh Gopal,; Harith Ali Al Qayyum,; Ahmad Hakimi Tajuddin, (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2024)
The emotional well-being and mental health of students in the higher education sector have been greatly researched over the past few years since students are increasingly subjected to various stressors in their daily lives. One element of such stressors would be the impact of service quality within the educational institution itself. However, previous studies had mainly focused on the influence of service quality regarding student satisfaction or motivation and completely overlooked their emotional well-being. The purpose of this study is to examine the effect of service quality on the emotional well-being of students in higher learning institutions by employing the HESQUAL model to discern on whether emotional well-being is affected by service quality and if so, the level of its impact. Primary data have been utilised and collected through a questionnaire created according to the model discussed, and were analysed with a sample size of 105 students. The findings of this study showed that Service Quality Factors such as Physical Environment Quality, Administrative Quality and Quality of Support Facilities has an effect on the emotional wellbeing of students, supporting the objective of this study. The data illustrates how each change in the level of service quality influences a change in emotional well-being. However, it is clear that further investigations are required in the future since there are variables that could be improved upon.